Writing the World : On Globalization - Rothenberg, David, 1962-; Pryor, Wandee J. (MIT Press, 2005)
Globalism as a global exchange of art and ideas: essays, memoirs, fiction, and poetry by writers including Arundhati Roy, Bill McKibben, and Naomi Klein.